2002
DOI: 10.21273/horttech.12.1.38
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Apple Rootstocks on Tree Growth, Yield, Fruit Quality, Leaf Nutrition, and Photosynthesis with an Emphasis on `Fuji'

Abstract: Tree fruit rootstocks are used to influence precocity, tree size, fruit quality, yield efficiency, mineral uptake, and to withstand adverse environmental conditions. In this paper, we will briefly discuss the history and literature of apple (Malus domestica) rootstocks and their effects on scion tree growth, yield, fruit quality, leaf mineral nutrition, and photosynthesis. Then, the results of our long-term study on the effects of rootstocks on tree growth, yield, fruit quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 18 publications
6
38
0
1
Order By: Relevance
“…Trees grafted on MA and MC appears to have the lowest leaf macronutrient concentration. The same effect on the leaf concentration was also found in lower vigour rootstocks in apple [29, 32, 33]. Several researchers have shown that scion leaves of trees on more vigorous rootstocks have higher mineral (K, Mg) content than those on size-controlling rootstocks [32, 34].…”
Section: Resultsmentioning
confidence: 70%
“…Trees grafted on MA and MC appears to have the lowest leaf macronutrient concentration. The same effect on the leaf concentration was also found in lower vigour rootstocks in apple [29, 32, 33]. Several researchers have shown that scion leaves of trees on more vigorous rootstocks have higher mineral (K, Mg) content than those on size-controlling rootstocks [32, 34].…”
Section: Resultsmentioning
confidence: 70%
“…In contrast, the Malling-Merton 111 (MM.111) rootstock only reduces the size of the tree by roughly 20% (Wertheim 1998). Rootstock effects on scion disease susceptibility, photosynthetic activity (Fallahi et al 2002), and cold tolerance have also been reported (Webster and Wertheim 2003, and references therein).…”
Section: Introductionmentioning
confidence: 92%
“…Apple trees with different species of rootstocks, even with the same scion, had different leaf Cu content and fruit quality Chun et al, 2002;Fallahi et al, 2001Fallahi et al, , 2002. In view of this fact, rootstocks, which constitute the roots of apple trees, determine Cu uptake and accumulation in aboveground tissues, especially fruit.…”
Section: Introductionmentioning
confidence: 99%